A3.2 Anti-citrullinated proteins antibodies promote synovial fibroblast migration in rheumatoid arthritis. (13th February 2015) - Sun, M; Joshua, V; Hensvold, AH; Catrina, SB; Malmström, V; Amara, K; Wähämaa, H; Catrina, AI
Abstract : Background and objectives: The presence of anti-citrullinated proteins antibodies (ACPAs) in RA is associated with aggressive disease phenotype and bone destruction. As synovial fibroblasts (SFs) are considered key players of both synovial inflammation and bone destruction in rheumatoid arthritis (RA), we studied the effect of ACPAs on fibroblasts migration. Methods and materials: Human dermal fibroblasts (HDFs) were obtained from PromoCell. SFs were isolated from synovial tissue of RA patients (RASFs) by enzymatic digestion. ACPA positive and negative IgGs were separated from plasma of RA patients and monoclonal anti-citrullinated antibodies were generated from synovial fluid by single B-cells. Migration scratch assays were performed using either RASFs or HDFs to test the effect of ACPAs, anti-citrullinated protein monoclonal antibodies and appropriate negative controls. The effect of a phosphatidylinositide 3-kinase (PI3K) inhibitor (wortmanin), G-protein coupled receptor (GPCR) inhibitor (pertussis toxin), focal adhesion kinase (FAK) inhibitor (PF-573228) and Protein-arginine deiminase (PAD) inhibitor (Cl-Amidine) was tested. Light microscopy images were taken at base line and after 6 h incubation and analysed using NIH ImageJ to calculate migration index. Cytotoxicity and proliferation assay were done in parallel with migration assays. Results: ACPAs but not others IgGs than ACPAs induced a 3.9 ± 0.5 (mean ± SD) fold increase in HDFs and a 2.6 ± 0.5 (mean ± SD) fold increase in RASFs migration (p < 0.05). GPCR blocking completely abolished ACPAs effects. PI3K but not FAK blocking abolished ACPAs effects, with minimal residual fold increase of 1.4 ± 0.4 (mean ± SD). Inhibition experiments suggest that ACPAs mediated RASFs migration via GPCR-PI3K pathway. Pre-inactivated PAD totally abolished ACPAs effects suggesting that citrullination is crucial for ACPAs mediated RASFs migration. No difference in either cytotoxicity or proliferation rate were observed between different treatments. One out of three different anti-citrullinated monoclonal antibodies displayed similar migration promoting effects. Conclusion: We describe a novel effect of ACPAs, providing a link between synovial fibroblasts and the adaptive immune system. We further suggest that different fine specificities of the ACPAs might have distinct impact on disease pathogenesis.